Strategiczne aspekty zarządzania jakością oraz innowacji produktowej w przedsiębiorstwie - Nowak, Artur (Wydział Prawa i Administracji UAM, 1997)
Quality management and innovation are two important aspects of the company strategic posture. They are fundamental elements of the firm strategic identity. Companies tend to use the same organizational platform for quality and innovation processes execution. Organizational platform is a system within which various, focused and specialized, primary and supportive functions of the company are performed. Quality and innovation processes dovetail and reinforce each other within the company value chain. Effective innovation and quality result in strategic uniqueness of the company's assets and/or competences. Hence, if the enterprise can maintain an effective organizational platform, it will be able to create a sustainable competitive advantage. One of basic functions of the organizational platform is to ensure that added value is being created and shared between the company and its stakesholders. In order to be effective in this area the firm must be effective in increasing its ability to accumulate, retain, and release strategic assets and core competences contingently to strategic situation on the market.
Strategic espects of quality management and product innovation